GLOBALIZATION AND GENDER DISPARITIES: A SOCIAL, ECONOMIC AND POLITICAL PERSPECTIVE FOR SOUTH ASIAN COUNTRIES - Ahmed Naveed, Dr. Tanveer; Sarwar, Kamran; Sibt e Ali, Muhammad; Saqib Irshad , Muhammad (The journal of contemporary issues in business and government, 2022)
Panel data from 2000 to 2016 will be used in this study to assess the influence of globalization on gender inequality in South Asian countries. As a proxy for gender differences, the Gender Inequality Index (GII) is utilised; for globalizations, social, political, and economic globalizations indices are also employed. The Swiss Federal Institute of Technology in Zurich created these three-dimensional indicators, while UNDP created an index of gender inequality. In order to determine if a fixed effect or random effect model should be used, the Hausman specification test is used.In this experiment, the results indicated that random effects should be used instead of fixed effects. There is a negative and significant correlation between the independent variables, like social globalizations, Human development indexes, and the gender inequality index. While Economic globalizations, political globalizations, and the Gender Inequality Index have a positive but substantial correlation. Several theoretical and empirical research support the findings of this one. Gender inequality in South Asia is a major problem, and this report recommends strategies to assist alleviate the problem. Gender equality is a key component of the strategies aimed at enhancing the region’s growth through globalizations elevation.